Electrochemical CO2 conversion towards syngas: Recent catalysts and improving strategies for ratio-tunable syngas - Hua, Yani; Wang, Jingyi; Min, Ting; Gao, Zhan (Journal of power sources, 2022)
In recent years, carbon neutrality has received increasing attention to alleviate climate and environmental problems. Electrocatalytic CO2 reduction towards syngas can be an efficient and sustainable strategy to mitigate the greenhouse gas effect. While the challenges of this technique lie in its high overpotential, poor selectivity, and difficulty of accurate regulation for syngas composition ratio. In this review, we analyze the catalytic mechanisms of electrochemical CO2-to-syngas conversion, and introduce various types of catalysts for CO2RR towards syngas. Emphatically, the effective strategies to improve the catalytic efficiency of electrochemical CO2-to-syngas conversion have been comprehensively summarized, including surface modification of catalyst, structural design of double active sites catalysts, morphology control of catalysts, anodic reaction coupling, and combination of CO2 capture and CO2 reduction. Then, the strategies for large-scale electrochemical CO2 reduction are presented, involving the scalable production of catalysts and reactor engineering strategies for industrial application. Finally, the future development guidelines for electrochemical CO2-to-syngas conversion are discussed. Our review paves the way to develop efficient electrocatalysts for enhanced CO2-to-syngas conversion and application. •The catalytic mechanisms of CO2-to-syngas conversion are analyzed.•The various types of catalysts for CO2RR towards syngas are introduced.•The strategies to improve the catalytic efficiency have been summarized.•The future development guidelines for CO2-to-syngas conversion are discussed.